2017
DOI: 10.1097/igc.0000000000000974
|View full text |Cite
|
Sign up to set email alerts
|

Completing or Abandoning Radical Hysterectomy in Early-Stage Lymph Node–Positive Cervical Cancer

Abstract: In patients with clinically N0 early-stage cervical cancer with intraoperative detection of positive nodes, completing RHL followed by adjuvant (chemo-)radiotherapy may result in a better pelvic control compared with abandoning hysterectomy and treatment with chemoradiotherapy. However, if corrected for lymph node variables, treatment (RHL or CRT) was not associated with DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…The largest study included in the Surveillance, Epidemiology, and End Results (SEER) database shows that RH (followed by adjuvant RT) for patients with pelvic node‐positive disease does not benefit DFS and OS compared with RT 9 . In contrast, several studies found that RH may provide better pelvic control 10,11 . Although there was not patient with pelvic recurrences in the RH group, a higher overall recurrence rate was observed in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…The largest study included in the Surveillance, Epidemiology, and End Results (SEER) database shows that RH (followed by adjuvant RT) for patients with pelvic node‐positive disease does not benefit DFS and OS compared with RT 9 . In contrast, several studies found that RH may provide better pelvic control 10,11 . Although there was not patient with pelvic recurrences in the RH group, a higher overall recurrence rate was observed in the present study.…”
Section: Discussioncontrasting
confidence: 70%
“…More grade 3e4 complications were reported in the abandoned group (47% vs. 27% of cases), which the authors hypothesised to be due to increased radiation exposure [15]. In the most recent study, the authors compared the outcomes of 121 patients who underwent primary surgery in a 10-year period at two sites in Amsterdam [20]. Patients with intraoperatively detected lymph node involvement, in whom radical hysterectomy was aborted, were compared with patients whose procedure was completed and lymph node involvement detected by final pathology.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of multiple cervical cancer bio-markers, cervical cancer can be detected and treated early, and the incidence and mortality of cervical cancer have been significantly reduced [3, 4]. At present, the treatment of cervical cancer mainly focuses on surgery and radiotherapy, but the survival rates of patients with advanced stage is very low, and the 5-year survival rates of invasive cervical cancer is only 67% [5, 6]. Additionally, early cervical cancer has no obvious symptoms, which therefore increases the difficulty of diagnosis [7].…”
Section: Introductionmentioning
confidence: 99%